(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article provides opinions on the problems related to the development of the cotton textile industry, as well as the tasks that should be performed on the widespread involvement of modern technologies in the industry. In addition, the issues of finding foreign partners for selling products produced in the textile sector, and exporting products to the world market were highlighted. Also, scientific conclusions, proposals and recommendations aimed at solving existing problems in the field have been developed.